2007
DOI: 10.1016/j.micres.2006.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria associated with orchid roots and microbial production of auxin

Abstract: Associative bacteria of terrestrial (Paphiopedilum appletonianum) and epiphytic (Pholidota articulata) tropical orchids were investigated. Microbial community of epiphytic plant differed from that of the terrestrial one. Streptomyces, Bacillus, Pseudomonas, Burkholderia, Erwinia and Nocardia strains populated Paphiopedilum roots, whereas Pseudomonas, Flavobacterium, Stenotrophomonas, Pantoea, Chryseobacterium, Bacillus, Agrobacterium, Erwinia, Burkholderia and Paracoccus strains colonized Pholidota roots. Endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
0
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(146 citation statements)
references
References 21 publications
11
109
0
14
Order By: Relevance
“…76 Researchers have also documented that auxin is not only involved in initiation, but also enhanced root growth. 77,78 Further, orchid roots are typically inhabited by fungal 79 and bacterial 80,81 symbionts that synthesize IAA. In epiphytes, auxin-producing rhizobacteria are located in the protective velamen layer.…”
Section: Root Induction and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Researchers have also documented that auxin is not only involved in initiation, but also enhanced root growth. 77,78 Further, orchid roots are typically inhabited by fungal 79 and bacterial 80,81 symbionts that synthesize IAA. In epiphytes, auxin-producing rhizobacteria are located in the protective velamen layer.…”
Section: Root Induction and Growthmentioning
confidence: 99%
“…81 When provided with L-tryptophan, which is a common root exudate and an auxin precursor, these endophytic isolates generate copious amounts of IAA. 80 Researchers have clearly demonstrated that the IAA produced by these microorganisms is biologically active, promoting both root growth and seed germination.…”
Section: Root Induction and Growthmentioning
confidence: 99%
“…The root tissue was harvested during the summer. Roots were cut and disinfected according to the protocol described by Tsavkelova et al (2007a).…”
Section: Isolation Of Rhizoplane and Endophytic Bacteriamentioning
confidence: 99%
“…An aliquot (50 μL) of each dilution was transferred to Czapek agar medium (Tsavkelova et al, 2007a), supplemented with a filtered cyclohexamide antifungal solution (1.0 mg mL -1 ).…”
Section: Isolation Of Rhizoplane and Endophytic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation